Identidad cultural y su relación con la conciencia turística en la población de la ciudad de Iquitos, año 2023 - Vega Cardozo, Frank Arnold (2025)
In this research, the objective was to confirm whether the variables’ cultural identity and tourism awareness in the population of Iquitos during the year 2023 are positively and significantly related to each other. The study employs a quantitative approach with a descriptive-correlational scope, along with a non-experimental cross-sectional design. The study population consisted of adults residing in Iquitos, and since the population is infinite, a sample of 203 individuals was selected. The result yielded a Spearman correlation value of 0.639, which, according to Martínez & Campos (2015), corresponds to a positive and significant correlation of moderate degree. The sigma (bilateral) value was 0.00, confirming the significance of the correlation. Regarding the perception of cultural identity, 2.0% of respondents (4 individuals) consider it "low," 9.9% (20 individuals) classify it as "medium," and 88.2% (179 individuals) perceive it as "high." In relation to tourism awareness, 0.5% (1 individual) considers it "low," 3.9% (8 individuals) classify it as "medium," and 95.6% (194 individuals) consider it "high." These results demonstrate that the variables’ cultural identity and tourism awareness in the population of Iquitos in 2023 are positively and significantly related, suggesting that cultural identity plays an important role in tourism awareness among the inhabitants of Iquitos, which could have key implications for local tourism development.